Iron monatomic catalyst, preparation thereof and application of iron monatomic catalyst in ORR and zinc-air battery

The iron single atom catalyst prepared by co-precipitation, aging and gradient calcination treatment solves the problem of poor catalyst activity in zinc-air batteries, realizes efficient oxygen reduction catalysis, improves battery performance and stability, and provides cheap and easy non-precious metal catalyst solution obtained.

CN119315043AActive Publication Date: 2025-01-14CENT SOUTH UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411430284.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-14
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The poor activity and slow kinetic activity of the ORR catalyst in existing zinc-air batteries lead to the problems of scarce resources, high cost and poor stability in market applications. It is urgent to develop high catalytic activity. and long cycle life non-precious metal catalysts.

Method used

Using a preparation method of iron single atom catalyst, through co-precipitation reaction, aging and gradient calcining treatment, an iron single atom catalyst with excellent catalytic activity and stability is prepared, including solutions in components A, B, C and D. Co-precipitation, aging and two-stage gradient calcination are carried out to form iron nanoparticles with hollow cage-like structures, which improves the catalyst's limit current density, peak power and discharge specific capacity.

Benefits of technology

It achieves excellent catalytic activity and stability in zinc-air batteries, improves the battery's limit current density, peak power and discharge specific capacity, and provides a cheap and easy-to-get non-precious metal catalyst solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315043A_ABST
    Figure CN119315043A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of fuel cells, and particularly relates to a preparation method of an iron monatomic catalyst, which comprises the following steps: carrying out coprecipitation reaction on a solution containing a component A, a component B and a component C, and separating to obtain a precipitation product; aging the precipitation product in a component D solution, and separating to obtain an aged product; and then carrying out gradient calcination on the aged product to obtain the product. The component A comprises a compound # imgabs 0 # in a formula 1; the component B comprises at least one of a compound # imgabs 1 # hexacyanoferrate in a formula 2, dopamine and salts thereof; the component C comprises an iron source and a zinc source; the component D comprises a water-soluble compound with a fragment # imgabs2 # as shown in a formula 3; the invention also comprises the material prepared by the method and application of the material in ORR and fuel cells. Researches show that the material prepared by the preparation method has excellent catalytic activity and stability in the aspect of ORR, and when the material is assembled into a metal-air battery, excellent limiting current density, peak power and specific discharge capacity can be shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular to the field of zinc-air batteries. Background Art

[0002] As the idea of ​​green, low-carbon and environmental protection has become popular, people are eager to find clean energy that can replace traditional fossil fuels such as coal, oil and natural gas. Metal-air batteries have attracted much attention due to their high energy density, low cost and environmental friendliness, such as zinc-air batteries. The redox reaction (ORR) is an important process for electrochemical energy storage and conversion, but the poor activity and sluggish kinetics of its four proton-coupled electron transfer steps hinder the application of zinc-air batteries in the market, and therefore they are extremely dependent on the efficiency of the use of electrocatalysts.

[0003] At present, the electrocatalysts used in the market are mainly based on precious metal catalysts such as platinum (Pt), etc. However, these catalysts are scarce, expensive, and have poor stability, which is not conducive to the large-scale practical application of zinc-air batteries. Therefore, it is urgent to develop non-precious metal catalysts with high catalytic activity, long cycle life, and low cost and availability, such as transition metal-nitrogen-carbon (TM-CN) catalysts, where transition metal (TM) refers to iron (Fe), cobalt (Go), nickel (Ni), and manganese (Mn). So far, the iron single-atom catalyst Fe-NC has become one of the most promising candidate materials because of its rich catalytic reaction sites. Therefore, designing an iron single-atom catalyst with high catalytic performance is a prerequisite for realizing the market application of zinc-air batteries.

[0004] Although there have been many studies on iron single atom catalysts, new materials and preparation methods still need to be developed to achieve the synthesis of iron single atom catalysts with high catalytic activity and long cycle life. Summary of the invention

[0005] In view of the insufficient catalytic effect of existing iron-based ORR catalytic materials, the first purpose of the present invention is to provide a method for preparing an iron single-atom catalyst, aiming to prepare an ORR catalytic material with excellent limiting current density, peak power and discharge specific capacity.

[0006] The second purpose of the present invention is to provide an iron single-atom catalyst obtained by the preparation method.

[0007] The third object of the present invention is to provide the iron single atom catalyst used as an ORR catalyst and its application in preparing a metal-air battery.

[0008] A fourth object of the present invention is to provide a metal-air battery comprising the iron single-atom catalyst.

[0009] A method for preparing an iron single-atom catalyst comprises: subjecting a solution containing component A, component B and component C to a coprecipitation reaction, separating and obtaining a precipitated product; then aging the precipitated product in a component D solution, separating and obtaining an aged product; and then subjecting the aged product to a gradient calcination to obtain;

[0010] The component A comprises a compound of formula 1; the component B comprises at least one of a compound of formula 2, ferrocyanide, dopamine and its salt; the component C comprises an iron source and a zinc source; the component D comprises a water-soluble compound having a fragment of formula 3;

[0011] The gradient calcination process includes a first calcination process at a temperature T1 and a second calcination process at a temperature T2; wherein the temperature T1 is 300-500°C; the temperature T2 is 850-1200°C;

[0012]

[0013] The R1, R2, and R3 are independently H, alkyl, carboxyl, or substituted alkyl with substituents; the substituents include at least one of hydroxyl, alkoxy, amino, amidinyl, carboxyl, and phenyl.

[0014] The present invention innovatively co-precipitates component C, a bimetallic component containing iron and zinc, in component A and component B, and then ages it in component D before performing the two-stage gradient calcination treatment. This unexpectedly enables the preparation of an iron single-atom catalyst with ORR-adapted physical and chemical structural characteristics. For example, a material having abundant ORR catalytic active sites and uniformly distributed iron nanoparticles with an obvious hollow cage structure can be prepared. Studies have also shown that the material prepared by the preparation method has excellent catalytic activity and stability in ORR, and the material assembled into a metal-air battery can exhibit an ORR catalytic material with excellent limiting current density, peak power and discharge specific capacity.

[0015] In the present invention, R1 can be H, C1-C 10 The substituted alkyl group may be a group with a substituent on a saturated carbon chain of C1 to C6, such as a carboxyl group, an amino group, an indolyl group, etc. Studies have shown that the component A using an amino-substituted alkyl group can be combined with the process to further synergistically improve the limiting current density, peak power and discharge specific capacity of the material.

[0016] Preferably, in the component A, R1 is a carboxymethyl group. Studies of the present invention show that the combination of the preferred component A and the process of the present invention can obtain better synergistic performance, which helps to further improve the limiting current density, peak power and discharge specific capacity of the prepared material.

[0017] In the present invention, in the component B, R2 is a C1-C4 alkyl group. There is no particular requirement for the substitution position of R2, for example, it can be the 2nd, 4th or 5th position.

[0018] In the present invention, in the component C, the iron source is a water-soluble compound of divalent iron and / or trivalent iron. The water-soluble compound is, for example, at least one of sulfate, nitrate, chloride, and organic acid salt of the metal element.

[0019] In the present invention, the zinc source is a water-soluble zinc ion compound.

[0020] In the present invention, in the component C, the molar ratio of Fe / Zn is 0.02 to 3:1; further, it can be 0.03 to 2:1.

[0021] Preferably, the molar ratio of component A: component B and component C is 0.1-1.1:2-8:1; further, it can be 0.8-1:4-8:1.

[0022] In the present invention, the temperature in the coprecipitation stage is 15 to 45° C., and may be room temperature.

[0023] In the present invention, the coprecipitation reaction time is 0.5 h or more, and further 10 to 35 h. Considering the preparation efficiency, it can be further 20 to 30 h.

[0024] In the present invention, after the coprecipitation reaction, solid-liquid separation is performed to obtain a precipitated product, which is then subjected to a subsequent aging reaction.

[0025] In the present invention, the coprecipitation reaction can be innovatively placed in a solution of component D for aging treatment, which can further effectively regulate the physicochemical structure, grains, grain boundaries, and orientation of the material to obtain a hollow cage structure, provide more catalytic sites, synthesize new electrocatalysts, further improve their oxygen reduction catalytic performance, and improve their catalytic stability, limiting current density, peak power, and discharge specific capacity.

[0026] In the present invention, the component D comprises at least one of Formula 3-A and Formula 3-B;

[0027]

[0028] The research of the present invention shows that the use of formula 3-A as component D can be further combined with other technical processes to further enhance the ORR performance of the prepared material, which helps to further improve the material's limiting current density, peak power and discharge specific capacity.

[0029] In the present invention, the solvent in the component D solution is, for example, an aqueous solvent, such as water, or a mixed solvent of water and an organic solvent. The organic solvent is, for example, a water-soluble organic solvent, and may further be a C1-C4 alcohol, acetone, or the like.

[0030] In the present invention, the concentration of the solute in the component D solution is 2 to 10 g / L, preferably 4 to 7 g / L.

[0031] Preferably, the weight ratio of the precipitated product to component D is 1:1-15; further, it can be 1:1.5-5.

[0032] Preferably, the aging treatment temperature is 15 to 45° C., and may be room temperature.

[0033] Preferably, the aging treatment time is 0.5 h or longer, preferably 1 to 10 h, and further preferably 5 to 9 h.

[0034] In the present invention, after the aging reaction, solid-liquid separation is performed to obtain an aging product, which is then subjected to a subsequent two-gradient calcination treatment.

[0035] In the present invention, the aged product is innovatively subjected to the two-stage gradient calcination treatment, which can give the prepared material rich ORR-adaptive physicochemical characteristics and obtain better limiting current density, peak power and discharge specific capacity.

[0036] In the present invention, the gradient calcination process is carried out in a protective atmosphere.

[0037] In the present invention, the protective atmosphere is, for example, at least one of nitrogen and inert gas.

[0038] Preferably, the gas pressure in the gradient calcination stage is 1-2.5 MPa, and can further be 1.5-2 MPa. The present invention shows that under the preferred slightly positive pressure, the physical and chemical structure of the product can be further optimized, and its oxygen reduction catalytic activity can be further improved.

[0039] The temperature T1 is 340-460°C.

[0040] Preferably, the insulation time t1 at the temperature T1 is 1 to 6 hours, and can further be 1 to 3 hours.

[0041] Preferably, the temperature T2 is 900-1150°C.

[0042] Preferably, the holding time t2 at the temperature T2 is 1 to 8 hours, and can further be 2 to 4 hours.

[0043] The invention also provides an iron single-atom catalyst prepared by the preparation method.

[0044] The preparation method of the present invention can give the prepared material special physical and chemical characteristics suitable for ORR, and the material prepared by the preparation method has excellent activity and stability in ORR catalysis. When assembled into a zinc-air battery, excellent limiting current density, peak power and discharge specific capacity can be obtained.

[0045] The present invention also provides an application of the iron single-atom catalyst prepared by the preparation method, which is used as an ORR catalyst.

[0046] In the present invention, the iron single atom catalyst can be used as an ORR catalytic material based on conventional means, and then used to prepare an ORR catalytic device, such as a battery. For example, one application method of the present invention can be to use the iron single atom catalyst as an ORR catalyst to prepare a metal air battery, and further a zinc air battery.

[0047] The present invention also provides an electrode for a metal-air battery, which comprises the iron single-atom catalyst prepared by the preparation method.

[0048] The electrode of the present invention, except for the iron single-atom catalyst, may have other components and parts known to the public.

[0049] The present invention also provides a metal-air battery, which comprises an electrode containing the iron single-atom catalyst of the present invention.

[0050] The metal-air battery of the present invention, except for the iron single-atom catalyst of the present invention, may have conventional structures, components and ingredients in other aspects.

[0051] In the present invention, the metal-air battery may further be a zinc-air battery.

[0052] Beneficial Effects

[0053] The present invention innovatively subjects component A of formula 1, component B of formula 2 and component C of Zn-Fe to a coprecipitation reaction, then subjects the coprecipitated reaction product to an aging reaction with component D, and then subjects the catalyst to a two-gradient calcination treatment. Thus, an iron single-atom catalyst prepared by a new preparation method can be unexpectedly obtained, which provides new preparation materials and preparation ideas, and further improves its catalytic activity and stability in oxygen reduction catalysis.

[0054] In the present invention, based on the new preparation method, the physical and chemical structure of the product can be further optimized by further optimizing and controlling component A, component B, component D and calcination mechanism, so that it can show better performance in oxygen reduction catalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1: SEM image of the sample obtained in Example 1;

[0056] Figure 2 : ORR reaction CV diagram of the sample obtained in Example 1;

[0057] Figure 3 : LSV diagram of ORR reaction of the sample obtained in Example 1. DETAILED DESCRIPTION

[0058] The specific steps of the present invention are described below by way of examples. It should be understood that these examples are only for illustrating the present invention and are not intended to limit the scope of the present invention in any way. Various processes and methods not described in detail in the present invention are conventional methods known in the art.

[0059] In the present invention, the raw materials selected can be purchased from commercial sources. In addition, the present invention has no special requirements on the chirality of the raw materials, and can be conventional meso or racemic raw materials.

[0060] Example 1

[0061] Step (1): Coprecipitation

[0062] The molar ratio of component A (Formula 1-A, which is Formula 1 wherein R1 is carboxymethyl) and component B is 0.92:4:1. and component C (a mixture of ferrous sulfate and zinc nitrate with a Fe / Zn molar ratio of 0.035:1, the molar amount of component C is based on the total molar amount of Fe+Zn) are dispersed in water (in the initial stage, the concentration of component A can be 2±0.5 g / L), and co-precipitated by stirring at room temperature for 24±2 h, followed by solid-liquid separation to obtain a precipitated product;

[0063] Step (2): Aging

[0064] The precipitated product obtained in step (1) is placed in a solution of component D (Formula 3-A) (the concentration of component D is 4 g / L), wherein the weight ratio of the precipitated product to component D is 1:1.5; then stirred and aged at room temperature for 8 hours; then solid-liquid separation is performed to obtain an aged product;

[0065] Step (3): Two-stage gradient processing

[0066] The aged product obtained in step (2) is placed in a tubular furnace, and an Ar inert atmosphere is introduced to fill the tube with the inert atmosphere to saturation, and the temperature is increased to 300°C (marked as T1) at a heating rate of 5°C / min, and kept warm for 2h (marked as t1), and then the temperature is increased to 900°C (sintering temperature T2) at a heating rate of 5°C / min, and then kept warm for 3h (marked as t2) to obtain an iron single-atom oxygen reduction catalytic material (active material).

[0067] According to GB / T 24533-2019, the specific surface area of ​​the obtained material is measured to be 587.9m 2 / g; a rotating disk electrode was used, and the prepared active material was used as the working electrode (the active material, conductive carbon black, and polytetrafluoroethylene were uniformly mixed into a uniform slurry at a mass ratio of 2:1:1, and the slurry was coated on a sheet pressed from nickel foam and gas diffusion membrane, and the electrode loading was 1 mg cm -2 The catalytic performance was tested in a three-electrode system. The limiting current density of ORR was tested in a 0.1 M KOH system. The results are shown in Table 1.

[0068] The final active material, conductive carbon black, and polytetrafluoroethylene were uniformly mixed in a mass ratio of 2:1:1 to form a uniform slurry, and the slurry was coated on a sheet pressed from nickel foam and gas diffusion membrane. The electrode loading was 1 mg cm -2 The air positive electrode was made, the polished zinc sheet was used as the metal negative electrode, and 6M KOH + 0.2M Zn (Ac) 2 was used as the electrolyte. The Lanbo electrochemical test system was used at a temperature of 25 ° C and the -2 The assembled zinc-air battery was tested under a large current of , and the results are shown in Table 1.

[0069] Example 2

[0070] Compared with Example 1, the only difference is that the type of component A is changed. The experimental groups are:

[0071] Group A: Component A is of formula 1-B, and its structure is

[0072] Group B: Component A is of formula 1-C, and its structure is

[0073] The test was carried out in the manner of Example 1, and the results are shown in Table 1.

[0074] Example 3

[0075] Compared with Example 1, the only difference is that the type of component B is changed. The experimental groups are:

[0076] Group A: Component B is potassium ferrocyanide;

[0077] Group B: Component B is dopamine hydrochloride;

[0078] The test was carried out in the manner of Example 1, and the results are shown in Table 1.

[0079] Example 4

[0080] Compared with Example 1, the only difference is that the type of component D is changed, specifically, component D is replaced by Formula 3-B, and other operations and parameters are the same as Example 1. The test is carried out in the manner of Example 1, and the results are shown in Table 1.

[0081] Example 5

[0082] Compared with Example 1, the only difference is that the conditions of step 3 are changed, and the experimental groups are:

[0083] Group A: T1 is 450℃, time t1 is 1.5h; temperature T2 is 1150℃, time t2 is 2h;

[0084] Group B: T1, T2 heating and heat preservation stages are carried out under slightly positive pressure, the pressure is 1.5-2MPa;

[0085] Other operations and parameters are the same as in Example 1.

[0086] Example 6

[0087] Compared with Example 1, the only difference is that in step 1, the molar ratio of component A, component B and component C is 1:8:1, and the molar ratio of Fe / Zn in component C is 2:1;

[0088] In step 2, the weight ratio of the precipitated product to component D is 1:5; the aging time is 6 hours;

[0089] Other operations and parameters are the same as in Example 1.

[0090] Comparative Example 1

[0091] Compared with Example 1, the only difference is that in step (1), component A is not added, and other operations and parameters are the same as in Example 1.

[0092] Comparative Example 2

[0093] Compared with Example 1, the only difference is that in step (1), zinc sulfate is not added to component C, and the missing zinc is supplemented by the iron in an equimolar amount. Other operations and parameters are the same as in Example 1.

[0094] Comparative Example 3

[0095] Compared with Example 1, the only difference is that step (2) is not performed, and the precipitated product of step (1) is directly used as a raw material for the gradient roasting treatment of step (3). Other operations and parameters are the same as those of Example 1.

[0096] Comparative Example 4

[0097] Compared with Example 1, the only difference is that step (2) is not performed, and component D in step 2 is directly added to the coprecipitation system in step 1, and the precipitated product is directly used as a raw material for the gradient roasting treatment in step (3). Other operations and parameters are the same as in Example 1.

[0098] Comparative Example 5

[0099] Compared with Example 1, the only difference is that in step 2, component D is replaced with an equal weight of perchloric acid, and other operations and parameters are the same as in Example 1.

[0100] Comparative Example 6

[0101] Compared with Example 1, the only difference is that in step 3, no two-stage gradient calcination treatment is performed, that is, the temperature of T1 is set to be the same as T2, and other operations and parameters are the same as Example 1.

[0102] Comparative Example 7

[0103] Compared with Example 1, the only difference is that in step 3, no two-stage gradient calcination treatment is performed, that is, the temperature of T2 is set to be the same as T1, and other operations and parameters are the same as Example 1.

[0104] The test results of each case are shown in Table 1:

[0105] Table 1

[0106]

[0107]

[0108] As can be seen from Table 1, the present invention innovatively subjects components A, B and C to a co-precipitation reaction, and then subjects the co-precipitated reaction product to an aging reaction with component D, followed by a two-gradient calcination treatment, thereby unexpectedly obtaining an iron single-atom catalyst prepared by a new preparation method, providing new preparation materials and preparation ideas, and further improving its catalytic activity and stability in oxygen reduction catalysis.

Claims

1. A method for preparing an iron single-atom catalyst, characterized in that: A solution containing component A, component B and component C is subjected to a coprecipitation reaction to separate and obtain a precipitated product; Then aging the precipitated product in the component D solution to separate and obtain an aged product; Then the aged product is subjected to gradient calcination to obtain; The component A comprises a compound of formula 1; the component B comprises at least one of a compound of formula 2, ferrocyanide, dopamine and its salt; the component C comprises an iron source and a zinc source; the component D comprises a water-soluble compound having a fragment of formula 3; The gradient calcination process includes a first calcination process at a temperature T1 and a second calcination process at a temperature T2; wherein the temperature T1 is 300-500°C; the temperature T2 is 850-1200°C; The R1, R2, and R3 are independently H, alkyl, carboxyl, or substituted alkyl with substituents; the substituents include at least one of hydroxyl, alkoxy, amino, amidinyl, carboxyl, and phenyl.

2. The method for preparing the iron single atom catalyst according to claim 1, characterized in that: In the component A, R1 is H, C1-C 10 Alkyl, carboxyl or substituted alkyl, the substituted alkyl is a group with a substituent on a saturated carbon chain of C1 to C6, the substituent is a carboxyl, amino, indolyl or the like; Preferably, in the component B, R2 is a C1-C4 alkyl group; Preferably, in the component C, the iron source is a water-soluble compound of divalent iron and / or trivalent iron; The zinc source is a water-soluble zinc ion compound; Preferably, in the component C, the molar ratio of Fe / Zn is 0.02 to 3:1; Preferably, the molar ratio of component A: component B and component C is 0.1-1.1:2-8:1; Preferably, the temperature in the coprecipitation stage is 15 to 45°C; Preferably, the coprecipitation reaction time is more than 0.5 h.

3. The method for preparing the iron single atom catalyst according to claim 1, characterized in that: The component D comprises at least one of Formula 3-A and Formula 3-B; 4. The method for preparing the iron single atom catalyst according to claim 1 or 3, characterized in that: The concentration of the solute in the component D solution is 2 to 10 g / L; preferably 4 to 7 g / L; Preferably, the weight ratio of the precipitated product to component D is 1:1 to 15; Preferably, the temperature of the aging treatment is 15 to 45°C; Preferably, the aging treatment time is more than 0.5 h.

5. The method for preparing the iron single atom catalyst according to claim 1, characterized in that: The gradient calcination process is carried out in a protective atmosphere; Preferably, the gas pressure in the gradient calcination stage is 1 to 2.5 MPa; Preferably, the holding time t1 at temperature T1 is 1 to 6 hours; Preferably, the holding time t2 at temperature T2 is 1 to 8 hours.

6. An iron single atom catalyst prepared by the preparation method according to any one of claims 1 to 5.

7. Use of an iron single atom catalyst prepared by the preparation method according to any one of claims 1 to 5, characterized in that: It was used as an ORR catalyst.

8. The use according to claim 7, characterized in that It is used as an ORR catalyst to prepare metal-air batteries and further zinc-air batteries.

9. An electrode for a metal-air battery, characterized in that: An iron single atom catalyst prepared by the preparation method according to any one of claims 1 to 5; Preferably, the metal-air battery is a zinc-air battery.

10. A metal-air battery, characterized in that: Comprising the electrode according to claim 9.

Citation Information

Patent Citations

  • Monatomic iron catalyst for electrocatalytic reduction of oxygen to water and preparation method and application of monatomic iron catalyst

    CN114792815A

  • Preparation method of nitrogen-rich porous submicron carbon sphere anchored iron monatomic cathode catalyst for zinc-air battery

    CN115799540A

  • ORR non-noble metal monatomic catalyst and preparation method thereof

    CN116404178A

  • MOF (Metal Organic Framework)-derived electrocatalyst, preparation and application in oxidation-reduction reaction

    CN116598516A

  • Supported nitrogen-phosphorus co-doped iron monatomic difunctional electrocatalyst and application thereof

    CN117334928A